Academic Hardiness, Stress, And Self-Efficacy in Relation to Career Goals Discrepancy of Pre-Service Teachers: A Path Analysis - Prospero B. Genosas III; Rustum A. Salvaña (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study is a quantitative inquiry aimed at testing a predictive model on career goal discrepancy among pre-service teachers (PSTs) in State Universities and Colleges (SUCs) in the Davao Region. A convenience sampling method was used to collect data from the PST sample. A survey questionnaires containing standardized scales were used to collect data. Results of the study showed that there was a high level of academic hardiness, a low level of academic stress, a high level of self-efficacy, and a moderate level of career goal discrepancy among the PSTs. The best-fitting path model indicated an indirect effect of self-efficacy and academic hardiness on career goal discrepancy. Self-efficacy and academic hardiness both negatively predicted academic stress which in turn positively predicted other types of stress such as physical and environmental stress.